Pemberdayaan Kader Dalam Upaya Pencegahan Stunting di Wilayah Kerja Puskesmas Cempaka - Santi, Eka; Azlina, Fitri Ayatul; Hasibuan, Nana Astriana; Firdausi, Rieh; Handayani Nasution, Tina; Nafi’ah, Rizka Hayyu; Adela SB, Rosyifa; Tsuraya, Nada; Meidiani, Ananda Humaira; Dzulkaidah, Azkalina Putri (Lembaga Dongan Dosen, 2024)
Stunting is a condition of chronic malnutrition before, during and after birth. This condition has a major impact on child development and cognitive abilities in the future. The discovery of stunting cases by cadres at toddler posyandus spread across each sub-district. The role of posyandu cadres is at the forefront in recognizing stunting incidents. This activity aims to improve the ability of posyandu cadres in preventing stunting incidents both during pregnancy and in caring for children. This activity is an activity in the application of health promotion to cadres which is a form of dedication of lecturers in applying their knowledge and supporting government efforts to improve human resources. The implementation of this activity involved 30 toddler posyandu cadres and pregnant women spread across 4 sub-districts, namely Cempaka Village, Sungai Tiung Village, Bangkal Village, and Palam Village. This activity was carried out in the Cempaka District Hall. Before the implementation of education about stunting, a pre-test questionnaire was filled out for 10 minutes, then continued with the presentation of the material and ended with a post-test questionnaire for 10 minutes. The results obtained showed that the knowledge of cadres about stunting increased after being given education. The knowledge of cadres with a high level of knowledge before training by 6.67% increased to 73.33%. The importance of knowledge possessed by cadres as the front line in preventing stunting.